Increased risk of rejection after basiliximab induction in sensitized kidney transplant recipients without pre‐existing donor‐specific antibodies – a retrospective study. (12th April 2019) - Goumard, Annabelle; Sautenet, Bénédicte; Bailly, Elodie; Miquelestorena‐Standley, Elodie; Proust, Barbara; Longuet, Hélène; Binet, Lise; Baron, Christophe; Halimi, Jean‐Michel; Büchler, Matthias; Gatault, Philippe
Summary: Depleting induction therapy is recommended in sensitized kidney transplant recipients (KTRs), though the detrimental effect of nondonor‐specific anti‐HLA antibodies is not undeniable. We compared the efficacy and safety of basiliximab and rabbit anti‐thymocyte globulin (rATG) in sensitized KTRs without pre‐existing donor‐specific antibodies (DSAs). This monocentric retrospective study involved all sensitized KTR adults without pre‐existing DSAs ( n = 218) who underwent transplantation after June 2007. Patients with basiliximab and rATG therapy were compared for risk of biopsy‐proven acute rejection (BPAR) and a composite endpoint (BPAR, graft loss and death) by univariate and multivariate analysis. Patients with basiliximab ( n = 60) had lower mean calculated panel reactive antibody than those with rATG ( n = 158; 23.7 ± 24.2 vs. 63.8 ± 32.3, P < 0.0001) and more often received a first graft (88% vs. 54%, P < 0.0001) and a transplant from a living donor (13% vs. 2%, P = 0.002). Risks of BPAR and of reaching the composite endpoint were greater with basiliximab than rATG [HR = 3.63 (1.70–7.77), P = 0.0009 and HR = 1.60 (0.99–2.59), P = 0.050, respectively]. Several adjustments did not change those risks [BPAR: 3.36 (1.23–9.16), P = 0.018; composite endpoint: 1.83 (0.99–3.39), P = 0.053]. Infections and malignancies were similar in both groups. rATG remains the first‐line treatment in sensitized KTR, even in the absence of pre‐existing DSAs.